Conditional Freedom Free Soil and Fugitive Slaves from the U.S. South to Mexico's Northeast, 1803-1861 - Mareite, Thomas (Brill, 2022)
While the literature on slave flight in nineteenth-century North America has commonly focused on fugitive slaves escaping to the U.S. North and Canada, Conditional Freedom provides new insights on the social and political geography of freedom and slavery in nineteenth-century North America by exploring the development of southern routes of escape from slavery in the U.S. South and the experiences of self-emancipated slaves in the U.S.-Mexico borderlands. In Conditional Freedom, Thomas Mareite offers a social history of U.S. refugees from slavery, and provides a political history of the clash between Mexican free soil and the spread of slavery west of the Mississippi valley during the nineteenth-century.